Perbedaan Strategi Pemasaran Standar vs Lokal (Standardization vs Localization) - Chesta Fillail Adabi (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
Advertising is an important element in the formation of values that will shape cultures and behaviors that ultimately determine people's consumption patterns. Advertising is now a powerful weapon for globalized companies to market their products to the world network and form a new era of colonization "Empire of Mind". It is at this point that these global brands need the help of advertising agencies with global networks currently led by six major groups to smooth out these goals. These global advertising agencies are then faced with the choice to create globally standardized ads or special ads that contain local content according to the culture of each country. The results show that in Indonesia advertisements featuring products from global brands are still dominated by global standardization advertisements. This result also occurs in advertisements that air in other countries, especially semiperipheral and peripheral countries. The results also corroborate the Global Consumer Culture Theory which states that global brands will use more uniform and standardized advertisements to reach the entire market. This strategy aims to shape new norms, values, culture and habits. Ultimately, this is so that core countries can continue to offer a wide range of products to semiperipheral and peripheral countries.